BERZAKAT MELALUI AMIL DALAM PERSPEKTIF AL-QUR’AN DAN SUNNAH - Arif Zunzul Maizal (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2017)
Zakat, beside to the pillars of Islam and ritual-vertical worship, is a socialhorizontal worship. Because basically zakat is allowed to the ummah of Islam in order to strengthen the economics of Muslims. This matter can be seen from the cues of the meaning of zakat in the language of al-numuw (growing and developing). To relize it, zakat must be paid by muzakki in accordance to the system that has been established shari’a. Among the systems that have been neglected are the payer of zakat which is done through amil formed by the government. Because the zakat workers who are collected through amil then managed professionally will be able to make zakat as a power of potential economic for ummat economic empowerment. Based on the Law No. 38 of 1999 and revised into Law No. 23 of 2011, the Indonesian government has adopted a part of Islamic Shari'a about zakat. In the Law, it is stated that the institution which have authority to carry out the duty of the Country in the zakat management in Indonesia are the National Amil Zakat Agency (BAZNAS) with each level and the National Amil Zakat Institute (LAZNAS).